Pengaruh Engagement, Pengawasan Dan Disiplin Kerja Terhadap Kinerja Karyawan PD Jabarhadi Bengkulu - Lisa Rosalini; Ida Anggriani; Nurzam Nurzam (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of engagement, supervision and work discipline on the performance of PD JabarHadi Bengkulu employees both partially and simultaneously. Methods used are multiple linear regression, coefficient of determination (R2), hypothesis testing (t test and test f) with the help of SPSS (statistical package for social science) version 25.0 program. The sample in this study amounted to 37 respondents. The results showed that (a) Engagement has an effect on the performance of PD JabarHadi Bengkulu employees. It is proven by the regression coefficient of 0.253, the value of tcount > ttable (2.059 > 2.035) and a significant value of 0.047 <0.05. (b) Supervision affects the performance of PD JabarHadi Bengkulu employees. Evidenced by the regression coefficient of 0.272, the value of tcount > ttable (2.162 > 2.035) and a significant value of 0.038 <0.05. (c) Work discipline affects the performance of PD Jabar Hadi Bengkulu employees. It is evidenced by the regression coefficient of 0.223, the value of tcount > ttable (2.101 > 2.035) and a significant value of 0.043 <0.05. (d) Engagement, supervision and work discipline affect the performance of PD JabarHadi Bengkulu employees. It is proven by the value of Fcount > ttable (13,988 > 2,659) and a significant value of 0.0000 < 0.05.